Implementation determinants and strategies in integration of PrEP into maternal and child health and family planning services: experiences of frontline healthcare workers in Kenya - Wagner, Anjuli D.; Beima-Sofie, Kristin; Awuor, Mercy; Owade, Winnie; Neary, Jillian; Dettinger, Julia C.; Pintye, Jillian; Abuna, Felix; Lagat, Harison; Weiner, Bryan J.; Kohler, Pamela; Kinuthia, John; et al. (Frontiers in Reproductive Health, 2023)
Background: Delivery of PrEP to adolescent girls and young women (AGYW) and to pregnant women through maternal and child health (MCH) and family planning (FP) clinics is scaling up in Kenya. Evaluation of implementation challenges and strategies is critical to optimize delivery.We conducted focus group discussions (FGDs) with healthcare workers (HCWs) in MCH and FP clinics offering PrEP in a large implementation project in Kisumu, Kenya. Discussion guides were based on the Consolidated Framework for Implementation Research (CFIR). FGDs were audio recorded and transcribed. Directed content analysis was used to identify implementation challenges and strategies to overcome them.